Neutrosophic Digraph with Generalized Modus Tollens (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we generalize modus tollens method for neutrosophic digraph by using neutrosophic ruleand define degree of a vertex in neutrosophic digraph, Indegree of a vertex in neutrosophic digraph, out degree ofa vertex in neutrosophic digraph and generalized modus tollens are discussed.